CODESRIA Bulletin Online, No. 20, June 2021 - Neither Settler Nor Native: A Response to My Critics - Mamdani, Mahmood (CODESRIA Bulletin, 2021)
I am thankful to CODESRIA for arranging this thoughtful engagement with my new work, Neither Settler Nor Native: The Making and Unmaking of Permanent Minorities. My interlocuters have raised several key issues. A Gender Gap? According to Ndlovu-Gatsheni, ‘there is a gender gap in Mamdani’s work’. Thandika Mkandawire once told me that it was CODESRIA’s misfortune that just about every African scholar, whether lawyer, political scientist or novelist, felt compelled to pay homage to political economy. Even if someone wrote a love poem, he or she was likely to be asked: What about class? The result was that we had not only bad poets and political scientists but also bad political economists. It seems to me that the place of political economy has been taken by gender analysis. No matter the theme you write on, you are likely to be asked: What about gender? Then we used to say: Working people are most of humanity. Now we say: After all, women are half of humanity. The fact is that every person is multiply identified, by gender, class, race, and so on. There is no single majority; each of these identifications gives you a different majority. The identity salient at a given time gives us a particular majority. It is the articulation of these identities that we now refer to as “inter-sectionality”. At one General Assembly, there was even a suggestion that CODESRIA should not publish an article or book that did not include gender analysis. Some members wondered whether we were witnessing the making of a gender police. Someone reading Ndlovu-Gatsheni’s response could easily mistake him for a member of a new gender police. But police, as we know, are often unable to see what is not in front of them. I have never claimed to be a gender theorist. But neither have I stayed at arm’s length from gender analysis. My first published book was the result of a research paper I wrote as a graduate student. The Myth of Population Control: Family, Class and Caste in an Indian Village (Monthly Review Press, 1972) was an ethnographic study of changing gender and patriarchal relations in a village in Punjab. I sought to understand how rapid technolo- gical change in agriculture was changing social relations and in turn transforming the reproductive behaviour of different castes and classes. My first attempt to theorise gender as a central category in social and political analysis was a decade later, in the 1980s, as a member of a Gender Working Group formed by CODESRIA. Its four members included Samir Amin, Zene Tadesse, Marie Angelique Savanne and me. At the first meeting, I presented the draft of a conceptual essay. I recall the title as ‘Gender and the Division of Labour’. I ended up being harshly criticised by my colleagues for pursuing an approach they thought had subordinated gender to class analysis. This was before the emphasis on ‘intersectionality’ became popular. The outcome did deter me from trying to produce theory on gender, but not from using gender as an analytical cate- gory in research on themes that I thought would be enriched by it. There were two such thematically driven research efforts. The first was on the relationship between the division of labour (gendered and patriarchal) and the process of capital accumulation. From 1980 to 1985, when I taught at Makerere University, I carried out ethnographic work (we then called it ‘field work’) in eight individual villages in different parts of Uganda. Two of these (a study of Amwoma in Lango and another of Kitende in Buganda) were published as two separate articles in Mawazo, the journal of the Faculties of Arts and Social Sciences at Makerere. I focused on the changing division of labour within families (both monogamous and polygamous). My core interest was in processes of social differentiation, and was driven by one question: Why do some peasant households become rich while most get impoverished? When I returned to Uganda after the NRM took office in 1986, I got together with a number of students and expanded the research to many more villages throughout the country. We gathered over 2,000 responses to the same questionnaire over several years. They remain in a box in my study in Kampala, unprocessed, mainly because I had a strong feeling that the result was unli- kely to yield any new question; repetition would not be productive. My second encounter with gendered research was driven by an interest in the question of group rights. It followed my involvement in the National Commission on Local Government, which I chaired from 1986 to 1988. The Commission led me to study the affirmative action programme introduced by the new government, the NRM, which included special parliamentary representation for historical minorities (women, workers, handicapped per- sons, etc.). My writing explored the contradictory effects of officially sanctioned representation: Would affirmative action empower marginalized groups through self-representation or disempower them by turning their representa- tives into so many de facto state agents, leaving these same minorities leaderless? I pursued this theme in several public meetings organised by the Centre for Basic Research (CBR) on Uganda’s experience with gender-based representation in Parliament. I also wrote a few articles on the subject, though in relatively obscure journals. Ndlovu-Gatsheni is understandably unaware of these publications and meetings since they were all under the radar, so to say. But I mention these as background to the question that Ndlovu-Gatsheni is interested in: Why do I not write of gender in Neither Settler Nor Native? This is certainly not because of a lack of reflection on the relationship between gender and extreme violence, the latter being the central thematic preoccupation of the book. The process of reflection led me to conclude that I could not just ‘add’ gender to race, tribe, religion, this time not even to class. I will spell out here the different steps in my reflection. Whereas I had come across instances of members of a self-defined race or tribe or religion dream of a genocidal path to a future without the other, I had yet to come across an instance where either gender, male or female, had imagined such a future, let alone tried to bring such a genocidal nightmare to life. The reason seemed clear to me: neither men nor women can survive without the other. Our future, as men or women, lies in co-existence. This posed a wholly different set of questions, pointing to a hitherto unfamiliar terrain. Historically, it seemed to set gender apart from other forms of politicised identities, such as tribe, race, etc. Gender needed to be thought through in greater depth—pre-class, pre-state or pre-polity. It also pointed away from genocidal tendencies to pos- sibilities of co-existence amidst tension. I shared these thoughts with students and colleagues at Makerere Institute of Social Research, and concluded that the question of gender in a study of extreme violence required a fresh approach. Such an approach would have to begin with the above reflection. Structure Without Agency In spite of the great generosity and insight with which he has mapped the intellectual journey leading to the publication of Neither Settler, I found the review essay by IB (which is how Abdallah Ibrahim is known in the CODESRIA community) puzzling. If Ndlovu-Gatsheni could see only what lay in front of him, IB seemed not to register my central preoccupation as stated in the very book he is reviewing. IB has two concerns. I shall begin with the first. In his words, Mamdani ‘ends up focusing more on structure than historical agency. … This seemingly one-sided narrative in Neither Settler Nor Native comes out clearly in the South African and South Sudanese experience.’ I think a re-reading may help clarify this doubt. There is a detailed analysis of ‘historical agency’ in Neither Settler, particularly in the chapters on South Africa and South Sudan. I divide the South African response to apartheid into two historical periods—before and after the mid-1970s. Before the 1970s, anti-apartheid politics was largely derivative. Each racial group organised separately, as defined by apartheid power—Africans as ANC, Indians as Natal Indian Congress, Coloureds as Coloured People’s Congress, and whites as the South African Congress of Democrats. This was structure domi- nating agency. By uncritically embracing the architecture of apartheid, the resistance reproduced it. I argue that apartheid’s ideological hold on its victims was broken only in the 1970s. The key initiative came from the student movement, black and white. The starting point was when Black students under Biko left the liberal white student organisation, formed their own separate body, and went on to organise township dwellers, beginning with Soweto. Left in the wilderness, radical white students turned to organising hostel workers on the fringes of these same townships. The turning point in anti-apartheid politics was the strikes that began in Durban in 1973 and the uprising in Soweto that followed in 1976. The Soweto Uprising unfolded under the banner of Black Consciousness (BC). Biko said: Black is not a colour; if you are oppressed, you are Black. This was the beginning of rethinking race not as destiny but as a historically produced agency. At the same time, there was nothing inevitable about the impact of BC on the anti-apartheid struggle. BC could have led to a nation-state consciousness—claiming that South Africa is a Black nation, of the Black majority, thus reifying and essentialising Black as a trans-historical identity. Instead, it led to an epistemological awakening— the consciousness of Black as a historical political identity. Afrikaners, too, made a journey from being junior partners of British colonialism to being part of the anti-apar- theid coalition. Even here, there was no consensus. The rift inside the Afrikaner community was demonstrated by the publication of a book, My Traitor’s Heart (1990), authored by Rian Malan, a great-grandson of a former Boer state president. Malan was a crime reporter for the Johannesburg paper, The Star. His beat covered black townships. Each chapter of his book focused on a specific type of what was then called black-on-black violence. One chapter was devoted to The Hammer Man, a big black man who wielded a heavy hammer to smash the skull of his victims, all equally black, but all poor people who would yield small pittances. Malan’s subtext was not difficult to decipher: If they can do this to their own, what will they do to us if given half a chance? There was nothing structurally inevitable about any of the above developments. Indeed, these historical actors began the process that would lead to an undermining of existing structures. I call this shift ‘the South African moment’. I argue that its birth in the 70s and 80s was marked by a three-fold shift in vision. One, from simple opposition, its opponents looked for an alternative to apartheid; rather than being content with turning the world upside down, they dared to think of a different world. Two, from a state of the majority—the national majority, the black majority—the resistance began to think of creating a state of all the people. Finally, from opposition to whites, the resistance went on to oppose white power. In Neither Settler, I suggest we think of 1994 as marking the birth of a new political community. The alternative would have been to rupture the existing community into two separate ones, as indeed happened in Sudan. The par- tition of South Africa into two separate political communities, one for victims and the other for perpetrators, one for blacks and the other for whites, would have reproduced the structures created under apartheid. Neither a modified reproduction nor a transformative impulse was a given. Let us not forget that, in 1994, Afrikaners too were divided about the future, with a minority asking for a homeland, where Afrikaners would have their own state. The anti- apartheid movement chose a different future, a common future for survivors of apartheid, who as Ndlovu-Gatsheni notes, often described themselves as a ‘rainbow’. In my words, they were no longer just victims who had survived, but ALL were survivors, whether victims, perpetrators, beneficiaries or bystanders. It seems to me that this vision was shared in its essentials by John Garang in South Sudan. Garang’s clearest statement of his vision on the historical nature of political identity—leading to his call for a ‘New Sudan’—was articulated in his address to representatives of the Northern Sudanese opposition at the meeting in Koka Dam. Garang challenged his audience to think of building an alternative political identity, other than one based on race and tribe. But Garang was murdered. The road he pointed to was not taken. It remains, however, not buried in the sands of history, but there to be opened by future generations who may learn from it. When it comes to the dialectic of structure and agency, my central concern in Neither Settler is precisely this: if our agency is structured and blunted by history, is it possible for us as historical subjects to recoup agency through an understanding of the nature of these structural constraints so we may reshape that very structure and rethink and remake the future? I state in the book that I refuse to think of structure as a Foucauldian prison in which historical subjects are fêted to live out their lives, like mice in a cage. Indeed, IB takes note of my claim to being an ‘incorrigible optimist’. No optimist can be an unthinking prisoner of historical structures. IB suggests that the lessons I draw from South Africa and South Sudan are more ‘prescriptive’ than analytical, and that they are belied by the present reality of South Africa. Forms of political identity, I have argued and my interlocuters note, are not artifacts of the market or sediments of cultural communities of meaning, but are linked to historically changing forms of the state. South Africa faced a dual political challenge in 1994: I describe the two issues as ‘deracialisation’ and ‘detribalisation’. IB focuses only on the former, and suspects that my analysis is contaminated by some kind of a romantic embrace of 1994. But if we look at the dual legacy of 1994, only ‘dera- cialisation’ gives us ground for optimism; the same cannot be said of the failure to detribalise. The outcome of this failure, called ‘xenophobic’ violence, highlights the depth of the challenge confronting the unfinished political transition. That this violence is more against the ‘tribal’ rather than the ‘racial’ other should be reason for sober reflection. I will return to this towards the end of this essay. IB’s second and parting critique is that Neither Settler does not address the question of social (economic) justice. In a rhetorical flourish, he laments the call for creating a political community of ‘undifferentiated survivors’: to quote IB, ‘the self-described “incorrigible optimist” has crafted a continental and global pathway to an imagined political community sans class struggle’ presumably to leave us with a ‘seemingly one-size-fits-all prescription…’. Alas, concludes IB, this ‘prescriptive pathway … skirts an old leftist debate that was inspired by the Fanonist problematic, the notion of true and false decolonisation’. True, my engagement with the left is not on true and false decolonisation, but on the left’s limited understanding of political decolonisation. I call for both a broadening and deepening of how we think of political decolonisation. I ask that we deepen our understanding of political decolonisation beyond freedom from external political domination, to include an internal aspect, rethinking and remaking the political community by depoliticising and redrawing internal political boundaries (‘race’ and ‘tribe’) that were drafted during the colonial era. Will this give rise to a community of ‘undifferentiated survivors’, or to a differentiated community who are divided in their response to the demand for social justice? My only point is that, the more deracialised and detribalised the political community, the less likely will is its response to demands for social equality be along racial and tribal lines. The principal critique of 1994 is that there has been no social justice. I have stated that this critique both states a truism and misses the significance of the political rebirth that was 1994. I argue that we should see the rebirth as the beginning of political decolonisation, but not the end of decolonisation. Without social justice, the gains made in the political domain will not endure. At the same time, any move towards deracialisation and detribali- sation is sure to improve the chances of waging a struggle for social justice than what they were under apartheid. My claim is that a successful struggle for social justice will need to cut across the political divides imposed by race and tribe. Without political equality, the mobilisation for social justice will be fragmented along lines of race and tribe. It will more likely lead to an internal civil war. The result will stink, like the 1994 genocide in Rwanda or its mini version, the ongoing xenophobic violence in South Africa. Popular Sovereignty and the Nation-State I would like to close by engaging with questions raised by Adom Getachew, mostly in the context of ‘the rise and universalisation of popular sovereignty and democracy in the nineteenth and especially twentieth centuries’. Getachew recognises that the notions of democratic state and national self-determination have been ‘mutually entangled’ over the past century and a half. What, we may ask, is the consequence of this fact, that the principle of democratic majorities has come to life within the shell of the nation-state? The point is best made if we return to the South African transition. The post-apartheid elections in 1994 posed a big question: Who should have the right to vote? At stake were the political rights of hundreds of thousands, maybe over a million, migrant workers who had over decades come from neighbouring territories: Mozam- bique, Lesotho, Zimbabwe, Malawi and others. Migrants had been pivotal in worker mobilisation since 1973 and were among the driving forces of the trade union movement that followed, starting with FOSATU. The ANC had historically been in solidarity with migrants. The 1955 Freedom Charter had boldly proclaimed that ‘South Africa belongs to all who live in it’—to all its residents, not just to its citizens. In 1994, migrants voted. But, following 1994, Chief Gatsha Buthelezi and the Inkatha Freedom Party (IFP) took control of the Ministry of Internal Affairs. Step by step, they chipped away at the rights of non-citizen residents, disenfranchising them. They told black South Africans that their rightful gains in the post-apartheid era were being usurped by non-citizen residents pouring in from across the country’s borders. They thus set citizens against resi- dents. This is why, when post-apartheid violence erupted, its target was the tribal stranger, not the racial stranger. ‘Xenophobic’ violence is testimony to the two-sidedness of citizenship: just as it empowered some (citizens), it excluded others (migrants). The state form inherited from apartheid was bifurcated: the central state was racialised and the local state was tribalised. The reforms of 1994 moved towards deracialisation, but not detribalisation. The beneficiaries of that reform had no problem accepting that race should rightfully be depoliticised, but not tribe; far too many believe that tribal (customary) rights are part of an age-old African culture, and not part of the legacy of apartheid. I argue that the failure to detribalise the state also marked the state of South Sudan from its birth in 2011. Getachew is certainly right to point out that whereas Neither Settler aims critically to reflect on the nation, the first half of the couplet nation-state, more critical energy needs to be focused on the overriding power of the state, the second half of the couplet, : ‘Would a decentralised and confederal structure work to undo the pathologies of the nation-state?’ At the same time, she recognises that ‘federal structures that maintain the politicisation of tribal and ethnic identity would not move us far in this direction’, this being ‘one of the cen- tral lessons Mamdani draws from the experience of South Sudan’. Getachew calls on us to reflect further on the question of federalism. The way forward, I think, is to acknowledge that federalism has multiple forms. I have in mind two: territorial and ethnic. The territorial form of federation was the innovation of settler states in the West, which drew their populations increasingly from European states. In the US, the state was reformed after the Civil War. The constitutional amendments that followed created a single federal citizenship overri- ding the citizenship of different states. Henceforth, someone born in one state could migrate to another and have the same rights as a person who had not only been born there but also had never moved out of the state. Contrast this with the ethnic federalism characteristic of most African federal states, from Nigeria to Ethio- pia, where one’s rights, particularly to land, are derived from one’s ethnic belonging. Ethnic federations have simply turned the federal unit into a collection of so many ethnic groups, each claiming its right to self-de- termination. It resembles more the pre-Civil War confederacy in the US than the federal arrangement after it. True, decentralisation needs to go hand in hand with democratisation, whereby the notion of citizen gives way to a broader and more inclusive notion, that of the resident, as a bearer of political rights. That is the limit of my ambition in this book. Neither the reform of the state nor the modalities of how the nation may exist are part of the agenda my book seeks to address. My focus is the present day conjoined unity of the two, the nation-state. A separate reflection on either of its halves, the nation and the state, will have to be the focus of a different book.